Predictors of Mortality in Pediatric Acute Lymphoblastic Leukemia: Analysis of 1004 Cases - Ullah, Anwar; Ghafoor, Tariq; Ahmad, Ishfaq; Ahmad, Shakeel; Arshad, Awais (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Objective: To assess the predictors of treatment-related mortality (TRM) among pediatric acute lymphoblastic leukemia (ALL) cases in Pakistan. Methodology: This retrospective study was conducted in the Pediatric Oncology department at Combined Military Hospital Rawalpindi, Pakistan. All newly diagnosed ALL cases between the ages of one and 18 years from 1st January 2013, to 31st December 2022 were included in the study. Physical and demographic data of all subjects were obtained and treatment outcome in terms of any complications or mortality were recorded during the above mentioned period. All data were analyzed using SPSS software. Results: Among 1004 cases of ALL 636(63.3%) were males and 368(36.7%) were females. The mean age during the diagnosis was 5.76±3.60 years. Overall Mortality was 295 (29.4%) including 191/295(64.7%) TRM and 104(35.3%) relapse-related mortality. Among the TRM cases, 124/191(64.9%) expired during induction. The usual complication during induction was Neutropenic fever. In univariate analysis, malnutrition (P=0.043), high WBC count (P=0.011), reduced hemoglobin level (P=0.005), low platelet count (P=0.002), neutropenic sepsis (P=0.001), and hepatotoxicity (P=0.001), were found to be related to high induction mortality. On multivariate analysis, infection was the most significant predictor of mortality during the induction and post-induction period. Infection followed by bleeding was the most common cause of mortality. After a median follow-up of 49.94+34.04 months, the overall Survival and Disease-Free Survival rates at five years were 70.6% and 68.4% respectively. Conclusion. The main causes of TRM in pediatric ALL are Neutropenic fever and bleeding. Malnutrition, high WBC count, neutropenic sepsis, and hepatotoxicity are the main predictors of high TRM. Key Words: Pediatric, Acute Lymphoblastic Leukemia, Mortality, Treatment Related Mortailty